Characterization of the Entire Cystatin Gene Family in Barley and Their Target Cathepsin L-Like Cysteine-Proteases, Partners in the Hordein Mobilization during Seed Germination - Martinez, Manuel (American Society of Plant Biologists, 2009)
Plant cystatins are inhibitors of cysteine-proteases of the papain C1A and legumain C13 families. Cystatin data from multiple plant species have suggested that these inhibitors act as defense proteins against pests and pathogens and as regulators of protein turnover. In this study, we characterize the entire cystatin gene family from barley (Hordeum vulgare), which contain 13 nonredundant genes, and identify and characterize their target enzymes, the barley cathepsin L-like proteases. Cystatins and proteases were expressed and purified from Escherichia coli cultures. Each cystatin was found to have different inhibitory capability against barley cysteine-proteases in in vitro inhibitory assays using specific substrates. Real-time reverse transcription-polymerase chain reaction revealed that inhibitors and enzymes present a wide variation in their messenger RNA expression patterns. Their transcripts were mainly detected in developing and germinating seeds, and some of them were also expressed in leaves and roots. Subcellular localization of cystatins and cathepsin L-like proteases fused to green fluorescent protein demonstrated the presence of both protein families throughout the endoplasmic reticulum and the Golgi complex. Proteases and cystatins not only colocalized but also interacted in vivo in the plant cell, as revealed by bimolecular fluorescence complementation. The functional relationship between cystatins and cathepsin L-like proteases was inferred from their common implication as counterparts of mobilization of storage proteins upon barley seed germination. The opposite pattern of transcription expression in gibberellin-treated aleurones presented by inhibitors and enzymes allowed proteases to specifically degrade B, C, and D hordeins stored in the endosperm of barley seeds.